HUBUNGAN ANTARA REGULASI EMOSI DENGAN MIMPI PADA MAHASISWA PSIKOLOGI REGULER-2 UNIVERSITAS MERCU BUANA JAKARTA - Pipit Puspitasari; Erna Risnawati (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2019)
Dreams are a bridge between conscious and unconscious. The continuing hypothesis of dreams in the general form states that dreams reflect a situation of waking life — something that is the center of attention, thought, and everyday experience — especially stressors, personal attention and emotional conditions. Dreams are an affective symbol of a person's emotional condition, therefore research on dreams is mostly done to see how psychological the individual is. This study aims to determine the relationship between emotional regulation and dreams, especially emotional elements in dreams in the regular-2 student population of Mercu Buana University, Jakarta. Data collection was conducted on 174 respondents of UMB Regular Psychology-2 students using non-probability sampling techniques, and using two questionnaires, namely a dream questionnaire adapted from The Mannhein Dream Questionnaire and an emotional regulation questionnaire adapted from the Emotion Regulation Questionnaire. The results of this study indicate that there is a significant relationship between emotion regulation and reappraisal dimensions with dreams but there is no relationship between suppression and dream dimensions. The researcher assumes that respondents who carry out a reappraisal strategy may only see the situation or conflict that they face as a situation that is not too emotional but does not really solve the problem at hand. In this case it is possible for the respondent to have emotions that are not expressed through the use of the reappraisal strategy, because reappraisal is a strategy that is used where the emotional response becomes triggered or not, which can be explained that emotion appears but is reappraisal so that it is intercepted appear in a dream.